Effect on color stability and surface roughness of nanofiller dental composite after soaking in Bidara leaf (Ziziphus mauritiana Lam) ethanol extract: an experimental study - fitriyani, Sri; Nazilla, Cut Syahla; sundari, Iin; Diansari, Viona; Subhaini, Subhaini; Ningsih, Diana Setya; Rahmayani, Liana; Qamaruzzaman, Jasmina Binti (Universitas Padjadjaran, 2025)
Introduction: Dental composite resins offer aesthetic appeal and high wear resistance; however, their physical properties may diminish after exposure to colored foods or mouthwashes. We explore Bidara leaf (Ziziphus mauritiana Lam) extract as an alternative mouthwash due to its rich content of bioactive compounds. The study aims to analyze the color change and surface roughness of nanofiller composite resins after immersion in Bidara leaf ethanol extract. Methods: This research was an experimental study. The resin composite samples were divided into four groups; each group consisted of 3 specimens (n=3): Group 1 (negative control) immersed in distilled water; Group 2 (positive control) immersed in 0.2% chlorhexidine; and Groups 3 and 4 soaked in 4.5% and 20% ethanol extracts of Bidara leaf, respectively. The specimens were cylindrical with a diameter of 10 mm and a thickness of 2 mm. All specimens were the same size, shape, and color, with flat surfaces and no cracks or stains. Samples were immersed for two minutes daily over one month. Color changes were analyzed using a stereomicroscope and the CIELab color system with Adobe Photoshop, while surface roughness was assessed using atomic force microscopy (AFM). Results: Color changes show ΔE>3.3 indicating a visible difference. The most significant color change occurrs in Group 4, followed by Groups 3, 2, and 1. One-way ANOVA shows a statistically significant color change (p<0.05). Surface roughness also increases, with Group 4 (0.138±0.066 μm) displaying the greatest roughness compared to Group 3 (0.122±0.061 μm), Group 2 (0.122±0.076 μm), and Group 1 (0.054±0.012 μm). Based on the one-way ANOVA test, the results show no significant differences (p>0.05) between the pre- and post-immersion. Conclusion: Although changes in surface roughness were not statistically significant, the ethanol extract of Bidara leaf influences the color and surface roughness of the nanofiller dental composite.